AB0189 Polymorphisms in genes involved in the metotrexate action mechanism. are they associated with response/toxicity of the drug?. (23rd January 2014) - Moya, P.; Salazar, J.; Altés, A.; Corominas, H.; Diaz-Torne, C.; Castellví, I.; Geli, C.; Córica, M. E.; del Rio, E.; de Llobet, J. M.; Baiget, M.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic, systemic, inflammatory autoimmune disease of unknown etiology. Methotrexate (MTX) is the first-line treatment option for newly diagnosed RA patients. However, only 50–70% of the patients will respond to MTX therapy and up to one third will discontinue treatment because of toxicity. Objectives: Studying SNPs (single nucleotide polymorphisms) described in the literature for its possible role as biomarkers of response and / or toxicity to MTX, in Spanish patients diagnosed with rheumatoid arthritis. Methods: We analyzed 27 TagSNPs in 5 candidate genes ( DHFR, TYMS, MTHFR, ATI C and CCND1) involved in the action mechanism of MTX. We studied its association with the therapy-related efficacy and toxicity. One hundred and twenty-four adult patients with RA treated with MTX monotherapy were studied. TagSNPs within these genes were selected using bioinformatic tools and were genotyped using a 48.48 dynamic array on the BioMark system. Toxicity was measured as the time interval that MTX was administered. Efficacy was assessed using the DAS-28 EULAR response criteria. Results: Clinical data of the patients are shown in Table 1 . The univariate analyses showed significant association with toxicity in the dominant model with two TagSNPs in the ATIC gene: rs10197559 (P=0.05) and rs16853826 (P=0.04). Two TagSNPs in the MTHFR gene showed significant association with response in the dominant model: rs11121832 (P=0.02) and rs17421511 (P=0.02). Conclusions: Polymorphisms in the ATIC and MTHFR genes may be considered as putative pharmacogenetic markers in RA patients treated with MTX on monotherapy. References: Kinder AJ, Hassell AB, Brand J, Brownfield A, Grove M, Shadforth MF. The treatment of inflammatory arthritis with methotrexate in clinical practice: treatment duration and incidence of adverse drug reactions. Rheumatology 2005;44:61–6 Wessels JA, van der Kooij SM, le Cessie S, Kievit W, Barerra P, Allaart CF, et al. A clinical pharmacogenetic model to predict the efficacy of methotrexate monotherapy in recent-onset rheumatoidarthritis. Pharmacogenetics Collaborative Research Group. Arthritis Rheum 2007; 56: 1765–75 Acknowledgements: Societat Catalana de Reumatologia. Disclosure of Interest: None Declared